2016
DOI: 10.1002/jmri.25180
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the precision and reproducibility of ventricular volume, function, and mass measurements with ferumoxytol‐enhanced 4D flow MRI

Abstract: Purpose To compare the precision and inter-observer agreement of ventricular volume, function and mass quantification by three-dimensional time-resolved (4D) flow MRI relative to cine steady state free precession (SSFP). Materials and Methods With research board approval, informed consent, and HIPAA compliance, 22 consecutive patients with congenital heart disease (CHD) (10 males, 6.4±4.8 years) referred for 3T ferumoxytol-enhanced cardiac MRI were prospectively recruited. Complete ventricular coverage with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 51 publications
2
49
1
Order By: Relevance
“…This ultrasmall superparamagnetic iron oxide medication was developed to treat anemia but has shown promise as a contrast agent, although is not approved by the US Food and Drug Administration for such use. Ferumoxytol had been administered per established, albeit off‐label, institutional protocol in patients undergoing 4D flow for cardiovascular indications and is not required for our conical UTE acquisition . However, we suspect it may further enhance the signal‐to‐noise ratio (SNR) and overall image quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ultrasmall superparamagnetic iron oxide medication was developed to treat anemia but has shown promise as a contrast agent, although is not approved by the US Food and Drug Administration for such use. Ferumoxytol had been administered per established, albeit off‐label, institutional protocol in patients undergoing 4D flow for cardiovascular indications and is not required for our conical UTE acquisition . However, we suspect it may further enhance the signal‐to‐noise ratio (SNR) and overall image quality.…”
Section: Discussionmentioning
confidence: 99%
“…All scans were enhanced with ferumoxytol (Feraheme, AMAG Pharmaceuticals, Waltham, MA), injected intravenously before imaging as a slow infusion over 5–15 minutes using a diluted volume in normal saline (3 mg/kg with 1:5 dilution or 0.1 mL/kg) . Vital signs were monitored for 30 minutes after ferumoxytol administration in the radiology department or an inpatient unit under the supervision of an advanced cardiac life support (ACLS) or pediatric advanced life support (PALS)‐certified physician.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, ferumoxytol supports the acquisition of 4-dimensional images of the beating heart with Four-Dimensional, Multiphase, Steady-State Imaging with Contrast Enhancement (MUSIC) (Figure 16) (99). Similarly, comprehensive motion-compensated highly accelerated 4D flow MRI with ferumoxytol enhances the quality of 4-dimensional flow information with reduced respiratory motion artifacts in children with congenital heart disease (100, 101). …”
Section: Vascular Mr Imaging With Ferumoxytolmentioning
confidence: 99%
“…Further, a free-breathing volumetric comprehensive MRI yielding flow, function, and anatomic assessment in less than 10 min has been achieved (100). Additionally, ventricular mass may be quantified with this same technique (101). As a result, no special operator knowledge of cardiac anatomy is required, and the duration of anesthesia and complexity of the procedure for congenital heart MRI can be greatly reduced.…”
Section: Vascular Mr Imaging With Ferumoxytolmentioning
confidence: 99%
“…4D flow MRI allows the evaluation of blood flow including valvular regurgitation (Figure 4, left panel), quantification of biventricular volumes, function and mass, and visualization of intracardiac and extracardiac structures (70,71). A recent study demonstrated that RV volume, function, and mass can be quantified with 4D flow MRI with precision and inter-observer agreement comparable to that of cine Steady-State Free Precession (SSFP) (72). Whole heart 4D flow MRI also enables detection and visualization of both normal and abnormal right heart flow patterns (73).…”
Section: Innovations In Magnetic Resonance Imagingmentioning
confidence: 99%